GAMBARAN TINGKAT PENGETAHUAN IBU RUMAH TANGGA TENTANG PENYAKIT DEMAM BERDARAH DENGUE DI DESA AAN - Swandewi, Luh Gede Mira; Damayanti, Putu Ayu Asri; Eva Yanti, Ni Luh Putu (Coping: Community of Publishing in Nursing, 2021)
The dengue virus is the cause of dengue hemorrhagic fever (DHF) transmitted through the bite of female Aedes aegypti mosquitoes. The Mosquito Nest Eradication Program (PSN) is an effective activity in preventing the breeding of Ae mosquitoes. aegypti. Prevention of DHF starts at the household level, one of which has an important role in preventing DHF is the mother. Mother's knowledge about the symptoms of DHF and its handling is very important to prevent DHF complications in family members. The purpose of the study was to find out the level of knowledge of housewives about dengue fever in Banjar Sengkiding, Aan Village. Descriptive quantitative research with a sample of 30 people and selected using simple random sampling. Age 38.78 years is the average age of respondents, with 21 years the youngest age and 55 years the oldest age. The education level of the research respondents was the education level of elementary school 2 people (6.7%), junior high school 4 people (13.3%), high school 18 people (60.0%) and tertiary institutions were 6 people (20.0%). The level of knowledge of respondents obtained was a good level of knowledge of 6 people (20.0%), a sufficient level of knowledge of 23 people (76.7%) and a level of knowledge of less than 1 person (3.3%). The results showed the level of DHF knowledge in housewives in Banjar Sengkiding, Aan Village the majority were at the level of sufficient knowledge. The community is also expected to take part in counseling conducted by the health department, public health center.